Temporal changes on the effect of rock fragments in interrill soil loss: a simulation experiment and a simple descriptiv - Figueiredo, T. de (2018)
Soils with rock fragments have been studied under several aspects in the last years. Research shows that a single pattern in the erosional response of these soils to rainfalls is not always found. In order to contribute to the understanding of this topic, an experiment was carried out, simulating interrill areas covered by rock fragments. This paper specifically aims at presenting and discussing temporal changes on sediment exported from such areas, also introducing a simple descriptive model to represent soil loss temporal evolution. Small bottom perforated boxes, 612 cm2 area, were filled with a silt-loam fine earth, very poor in organic matter, covered with simulated rock fragments and leaned at 10% slope gradient. The experiment comprised the exposure to 240 mm natural rainfall of 48 boxes corresponding to selected combinations, 4 replicates each, of rock fragments cover (0, 17, 30 and 66%), size (2, 4 and 10 cm), form (rectangular and circular) and position (resting on top and embedded). During the experiment boxes were kept under near saturation soil water conditions. Water and soil exported from the boxes as infiltration, runoff, wash and splash were measured after each period of precipitation. Recorded values of soil loss plotted against precipitation, both expressed in cumulative terms, follow a sigmoid curve. This pattern of response was interpreted as a result of crust formation on soil surface exposed to rainfalls, a hypothesis suggested by observations during the experiment and confirmed at its end. Parameters of this model were related with rock cover and characteristics. The effect of rock fragments on soil loss varies with time, a conclusion that must be taken into account when interpreting either results from experiments with different durations or the evolution of stoniness on eroding surfaces.